PENGARUH LITERASI KONSUMEN DAN TINGKAT PENDIDIKAN TERHADAP KEPUTUSAN MENJADI NASABAH PADA BANK SYARIAH - Ahmad Mustajib (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2019)
This study aims to determine the effect of consumer literacy and education level on the decision to become a customer at a sharia bank in the Langensari sub-district community, Banjar city and to determine which variables of consumer literacy (X1) and education level (X2) affect the decision to become a customer at a sharia bank ( Y) in the community of Langensari District, Banjar City. Data were collected using a questionnaire using a Likert scale. The population of this research is people in Langensari sub-district with a total sample of 45 people and the method of determining the sample used is Simple Random Sampling. The analytical method used is multiple linear regression analysis. Partial test results show that consumer literacy (X1) has no effect on the decision to become a customer of Islamic banks with a significance value of 0.165 > 0.05 and a t value of -1.412 < from t table 2.0141. Testing the effect of education level (X2) on the decision to become a customer of a sharia bank partially has a significant effect. It can be seen from the results of the t test, where the t value for the variable Education Level is 2,968 > t table 2,0141, with a significance value of 0.005 < 0.05. The results of the study simultaneously show that consumer literacy (X1) and education level (X2) simultaneously have a positive effect on the decision to become a customer at a sharia bank (Y). indicated by the results of the F test at a significance level of 5% which obtained the calculated F value of 4.607 and the F table value of 3.23, so it can be seen that the calculated F value is greater than the F table value with a significance value less than 0.05 (0.005 <0.05).